Experimental Investigation on Strength and Durability of Graphene Nanoengineered Concrete. (22nd March 2021) - Dalal, Sejal P.; Dalal, Purvang
Highlights: Graphene is the wonder material of the century having excellent tensile strength. A Surfactant functionalised graphene is made from liquid shear exfoliation process. Sodium laureth sulphate and linear alkylbenzene sulfonates are used as surfactant.It is named as SLES-Graphene (SG). SG powder dispersed water solution is used to make concrete and then investigated. The SG Nanoengineered concrete has demonstrated very good strength. The results were validated by Analysis of Variants (ANOVA) for enhanced confidence. SG concrete may help to achieve a sustainable development in construction industry. Abstract: Graphene has emerged as one of the most promising nanomaterials because of its unique characteristic of being one of the thinnest yet the strongest material. The strength and durability of a novel surfactant functionalized graphene induced concrete composite has been investigated. The water stabilized graphene dispersion at dosages of 0.5, 0.6, 0.7, 0.8, 0.9, and 1 gm/l were used in concrete composites of nine different mixes. An increase of up to 95%, 55% and 27% is achieved in flexural, tensile and compressive strength respectively due to addition at 1 gm/l dosage of graphene. Vice versa, an increase in water absorption and shrinkage is also observed. The study directs towards yield of a graphene nanoengineered concrete which would be of utmost importance in coming years for a sustainable solution in the construction industry.